ENDONG BALAPAK - Fitri Wahyuni; Desfiarni Desfiarni; Herlinda Mansyur (FBS Universitas Negeri Padang, 2013)
Abstract This article aims at explaining and describing a dance artwork entitled Endong Balapak. This dance was derived from a tradition dance “Randai Salapan” in the area Gunuang Padang Panjang. This Randai Salapan dance uses large trousers and the trousers are beaten by hand, resulting in a unique sound. These trousers are called galambuak or galembong and also often called as Endong. On the other, Balapak, is the sound effect produced by Randai players when they beat their Endong. The Endong Balapak dance is an actualization of dancers’ aesthetic play in techniques and richness of motive in playing sound and movement in beating Endong. Thus, the aesthetic value appears intrinsically from Endong Balapak dance. The sources reproduction is Randai Salapan, with the object traditional artwork, and the type of dance is pure with non representative performance. Keywords: Endong Balapak, Randai Salapan and Creative Dance